Personality profiles and psychological adjustment in breast cancer patients. - Cerezo-Guzmán, María Victoria; Blanca-Mena, María José; Ferragut-Ortiz-Tallo, Marta (MDPI, 2020)
Dispositional personality characteristics may play a role in psychosocial adjustment to any disease, including cancer. Purpose: The purpose of this study is to identify personality profiles in breast cancer patients and to determine whether these profiles are associated with psychological adjustment or psychopathology. Methods: Participants were 109 women (mean age, 52.01) diagnosed with breast cancer. They completed the Millon Clinical Multiaxial Inventory-III (MCMI-III), the Life Orientation Test-Revised (LOT-R), the Satisfaction with Life Scale, and the Positive and Negative Affect Scales. Results: The analysis revealed two different personality profiles: (a) one group, comprising 38.23% of the sample, was characterized by paranoid, negativistic, and dependent personality traits and was considered as a “vulnerable group”; and (b) another group (61.77%) was characterized by compulsive, histrionic, and narcissistic personality traits and was considered as a “psychologically adjusted group”. The vulnerable group scored higher than the psychologically adjusted group on all clinical syndromes, with scores above 60 on the anxiety, somatoform, dysthymic, and bipolar scales (score on anxiety being above 75); in contrast, the psychologically adjusted group did not reach a base rate score of 60 on any of the clinical syndromes, showing no manifestations of psychopathology. Additionally, the vulnerable group scored lower than the psychologically adjusted group on optimism, life satisfaction, and positive affect, but higher on negative affect. Conclusions: The results suggest that personality traits could affect the psychological adjustment of breast cancer survivors. We discuss the implications of belonging to each group and highlight the importance of early identification of vulnerable women in order to facilitate clinical and psychological support
Keywords: Mamas - Cáncer; MCMI; Breast cancer; Clinical syndromes; Personality; Psychological profile; Well-being